THE RELATIONSHIP BETWEEN RESPONSE TIME NURSES PROVIDING PATIENT FAMILY SATISFACTION IN EMERGENCY ROOM RSUD KOTA BOGOR: HUBUNGAN ANTARA RESPONSE TIME PERAWAT DENGAN KEPUASAN KELUARGA PASIEN DI IGD RSUD KOTA BOGOR - Nining Fitrianingsih, Nining; Dewi Atikah, Dewi (Wijaya Husada, 2019)
Emergency is a condition or situation in the event of threatened or already on the adverse effects of such harm that resulted in further damage. Response time is the time between of the birth of a request addressed in other words can be called the response. The response is good for patients which is≤5 minutes. The purpose of researchers to knowif there is a connection between the response time nurses regarding satisfaction of the patient’s family. The research is a research sort of descriptive set of analytic quantitative, design of this research is cross sectional. The samples of this study are 170 respondents. The sampling in this study uses accidental sampling. The data collected are using a stopwatch and a questionnaire. The results of the 170 of the respondents is 66 of respondents (38,8%) obtained response time nurses and the satisfaction of family are satisfied. Response time fast but not really satisfied the are 41 respondent (24,1%), who received a response slow but was satisfied are as many 27 of the respondents (15,9%) and 36 of the respondent (21,2%) don’t feel satisfied and response time too late. The results of the analysis bivariate the use of the kendalls tau to the p value = 0.016 with significant is ≤0,05, H0 be rejected and have received, which means there is a connection between the response time a nurse with satisfaction the family in the emergency room hospital of Bogor Hospital. Conclusion of this research is a link between response time a nurse with satisfaction the family in the emergency room Bogor Hospital. PDF